Pengaruh Modernisasi Perpajakan, Pengetahuan Pajak, dan Persepsi terhadap Minat Penggunaan Konsultan Pajak. - Annisa Yourinda; Wajib Ginting (IKRAITH-EKONOMIKA, 2026)
Through the self-assessment system, the responsibility for fulfilling tax obligations is transferred to taxpayers, who are required to carry them out independently without reliance on other parties. In an effort to enhance the efficiency and transparency of tax administration, the government has implemented the Coretax Administration System as part of tax administration modernization. The implementation of this system may influence taxpayer behavior, including interest in utilizing tax consultant services. The present study aims to analyze the effect of Coretax-based tax administration modernization, tax knowledge, and taxpayers’ perceptions on the interest in using tax consultant services among individual taxpayers listed at KPP Pratama Bandung Tegallega. A total of 100 respondents were selected as the research sample, determined using the Slovin formula within a quantitative research approach. Data were analyzed using multiple linear regression with the assistance of SPSS. The findings indicate that tax administration modernization, tax knowledge, and taxpayers’ perceptions do not have a significant effect on the interest in using tax consultant services, either partially or simultaneously.